Phytochemicals in Human Health 2020
DOI: 10.5772/intechopen.88096
|View full text |Cite
|
Sign up to set email alerts
|

Coumarin Derivatives with Antimicrobial and Antioxidant Activities

Abstract: Coumarin derivatives are structurally interesting compounds for synthesizing antimicrobial and antioxidant agents. Starting from 4-methyl-7-hydroxycoumarin, several derivatives with these properties have been obtained through different reaction steps. Their molecular structures were established by Fourier-transform infrared spectroscopy and nuclear magnetic resonance spectroscopy. The synthesized coumarin derivatives exerted meaningful activities against Gram-positive and Gram-negative bacteria as well as stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…The second-highest relative intensity was that of the 1,3-benzodioxol-4-ol, a phenolic benzothiazole derivative, which approved various biological importance because of its anticancer, antimicrobial, and antioxidant activities [ 12 ]. The results showed the presence of higher content of coumarin, an aromatic heterocyclic organic compound, which is known for its antibacterial activity against both Gram-positive and Gram-negative strains, and its antifungal activity against Aspergillus niger and Candida albicans , besides it exhibited an appropriate antioxidant activity, as had been tested by the DPPH (2,2-diphenyl-1-picryl-hydrazyl-hydrate) in the radical scavenging activity assay [ 13 ]. Previous studies showed that silver nanoparticles loaded with 9-anthracenecarboxylic acid showed strong antifungal activity against Candida albicans [ 14 ] or antibacterial activity against human bacterial pathogens [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…The second-highest relative intensity was that of the 1,3-benzodioxol-4-ol, a phenolic benzothiazole derivative, which approved various biological importance because of its anticancer, antimicrobial, and antioxidant activities [ 12 ]. The results showed the presence of higher content of coumarin, an aromatic heterocyclic organic compound, which is known for its antibacterial activity against both Gram-positive and Gram-negative strains, and its antifungal activity against Aspergillus niger and Candida albicans , besides it exhibited an appropriate antioxidant activity, as had been tested by the DPPH (2,2-diphenyl-1-picryl-hydrazyl-hydrate) in the radical scavenging activity assay [ 13 ]. Previous studies showed that silver nanoparticles loaded with 9-anthracenecarboxylic acid showed strong antifungal activity against Candida albicans [ 14 ] or antibacterial activity against human bacterial pathogens [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, PLA/PLA_15UMB presented the lowest heat resistance probably due to a plasticizing effect of UMB and a diminution in the χ c in the bilayer system. Regarding the antioxidant capacity of the mono and bilayer films, LNPs produced the highest antioxidant activity in the monolayer formulations, while the combined incorporation of LNPs and UMB in the PLA bilayer films induced the highest antioxidant activity due to the synergistic effect of both additives [ 25 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four different PLA-based monolayer films were obtained by melt blending in a twin-screw microextruder (DSM Xplore 15 Micro Compounder, Xplore Instruments BV, Sittard, The Netherlands): neat PLA, two PLA nanocomposites with 3 wt% of CNCs or LNPs, and PLA active film with 15 wt% of UMB. CNCs, LNPs and UMB have been selected according to previous results obtained by the authors on separated or combined use of CNCs and LNPs in poly(lactic acid) [ 28 ], while the amount of UMB was selected on the basis of dispersibility results and its effect of transparency and antibacterial response when introduced in polymeric film formulations [ 25 ]. All based materials were dried prior processing in an air circulating oven at 50 °C overnight in order to eliminate moisture traces.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations